Postoperative Complications after Ileocecal Resection in Crohn's Disease: A Prospective Study From the REMIND Group. (February 2017) - Fumery, Mathurin; Seksik, Philippe; Auzolle, Claire; Munoz‐Bongrand, Nicolas; Gornet, Jean‐Marc; Boschetti, Gilles; Cotte, Eddy; Buisson, Anthony; Dubois, Anne; Pariente, Benjamin; Zerbib, Philippe; Chafai, Najim; et al.
Abstract : Objectives: We sought to determine the frequency of and risk factors for early (30‐day) postoperative complications after ileocecal resection in a well‐characterized, prospective cohort of Crohn's disease patients. Methods: The REMIND group performed a nationwide study in 9 French university medical centers. Clinical‐, biological‐, surgical‐, and treatment‐related data on the 3 months before surgery were collected prospectively. Patients operated on between 1 September 2010 and 30 August 2014 were included. Results: A total of 209 patients were included. The indication for ileocecal resection was stricturing disease in 109 (52%) cases, penetrating complications in 88 (42%), and medication‐refractory inflammatory disease in 12 (6%). A two‐stage procedure was performed in 33 (16%) patients. There were no postoperative deaths. Forty‐three (21%) patients (23% of the patients with a one‐stage procedure vs. 9% of those with a two‐stage procedure, P =0.28) experienced a total of 54 early postoperative complications after a median time interval of 5 days (interquartile range, 4–12): intra‐abdominal septic complications ( n =38), extra‐intestinal infections ( n =10), and hemorrhage ( n =6). Eighteen complications (33%) were severe (Dindo–Clavien III–IV). Reoperation was necessary in 14 (7%) patients, and secondary stomy was performed in 8 (4.5%). In a multivariate analysis, corticosteroid treatment in the 4 weeks before surgery was significantly associated with an elevated postoperative complication rate (odds ratio (95% confidence interval)=2.69 (1.15–6.29); P =0.022). Neither preoperative exposure to anti‐tumor necrosis factor (TNF) agents ( n =93, 44%) nor trough serum anti‐TNF levels were significant risk factors for postoperative complications. Conclusions: In this large, nationwide, prospective cohort, postoperative complications were observed after 21% of the ileocecal resections. Corticosteroid treatment in the 4 weeks before surgery was significantly associated with an elevated postoperative complication rate. In contrast, preoperative anti‐TNF therapy (regardless of the serum level or the time interval between last administration and surgery) was not associated with an elevated risk of postoperative complications.